Smallholder tree crops in Sierra Leone: Impacts on food consumption and nutrition - Bellin, Friederike (International Food Policy Research Institute, 1994)
Tree crops such as coffee, cocoa, and oil palm have been promoted for many years in Sierra Leone. Tree crop production was believed to be associated with improved nutritional status; significantly lower rates of malnutrition have been reported in Eastern Province (26.0 percent),1 which has been the leader in terms of tree crop production, than in Southern Province (33.4 percent), which has only recently started promoting tree crops (Sierra Leone, Government of 1978). Whether it is actually tree crop production or other factors that are mainly responsible for the improved nutritional status in Eastern Province has not yet been investigated, and, therefore, simple conclusions should not be drawn. The purpose of this study is to evaluate the impact of tree crop promotion on other agricultural production, income and expenditure patterns, and nutrition.